Trends in medicines procurement by the Brazilian federal government from 2006 to 2013 - Chama Borges Luz, Tatiana (PLoS One, 2017)
The costs of medicines pose a growing burden on healthcare systems worldwide. A comprehensive understanding of current procurement processes provides strong support for the development of effective policies. This study examined Brazilian Federal Government pharmaceutical procurement data provided by the Integrated System for the Administration of General Services (SIASG) database, from 2006 to 2013. Medicine purchases were aggregated by volume and expenditure for each year. Data on expenditure were adjusted for inflation using the Extended National Consumer Price Index (IPCA) for December 31, 2013. Lorenz distribution curves were used to study the cumulative proportion of purchased therapeutic classes. Expenditure variance analysis was performed to determine the impact of each factor, price and/or volume, on total expenditure variation. Annual expenditure on medicines increased 2.72 times, while the purchased volume of drugs increased 1.99 times. A limited number of therapeutic classes dominated expenditure each year. Drugs for infectious diseases drove the increase in expenditures from 2006 to 2009 but were replaced by antineoplastic and immunomodulating agents beginning in 2010. Immunosuppressants (L04), accounted for one third of purchases since 2010, showing the most substantial growth in expenditures during the period (250-fold increase). The overwhelming price-related increase in expenditures caused by these medicines is bound to have a relevant impact on the sustainability of the pharmaceutical supply system. We observed increasing trends in expenditures, especially in specific therapeutic classes. We propose the development and implementation of better medicine procurement systems, and strategies to allow for monitoring of product price, effectiveness, and safety. This must be done with ongoing assessment of pharmaceutical innovations, therapeutic value and budget impact.